Mycobacterial heat shock protein 65 (mbHSP65)-induced atherosclerosis: Preventive oral tolerization and definition of atheroprotective and atherogenic mbHSP65 peptides. Issue 1 (September 2015) - Grundtman, Cecilia; Jakic, Bojana; Buszko, Maja; Onestingel, Elisabeth; Almanzar, Giovanni; Demetz, Egon; Dietrich, Hermann; Cappellano, Giuseppe; Wick, Georg
Abstract Objective The aim of this study was to identify atherogenic and atheroprotective peptides of bacterial HSP60 [taking mycobacterial HSP65 (mbHSP65) as a potent paradigmatic representative] that could be used as candidates for an orally applied tolerizing vaccine against atherosclerosis. Methods ApoE−/− mice were immunized with mbHSP65 protein or peptides, given mbHSP65 orally and then kept either on chow or high cholesterol diet. Atherosclerosis was assessed by en face and immunohistological analysis. Anti-HSP autoantibodies were detected by ELISA. The number and in vitro suppressive function of splenic and lymph node regulatory T cells (Tregs) were analyzed by flow cytometry. Specific T cell reactivity against mbHSP65 protein or peptides was assessed by proliferation assay. Results Decreased lesion size was accompanied by (a) increased splenic Treg numbers; (b) increased interleukin (IL)-10 mRNA levels in the aorta; (c) increased levels of anti-mbHSP65 and anti-mouse HSP60 antibodies pointing to pro-eukaryotic HSP60 humoral crossreaction, not curtailed by oral tolerization; (d) most importantly, we identified and functionally characterized novel atherogenic and atheroprotective mbHSP65 epitopes. Conclusion Atheroprotective mbHSP65 peptides may be considered as potential candidates for the development of a tolerizing vaccine to prevent and treat atherosclerosis, while keeping protective immunity to non-atherogenic domains of mbHSP65 intact.